The barley anion channel, HvALMT1, has multiple roles in guard cell physiology and grain metabolism. Issue 1 (4th July 2014) - Xu, Muyun; Gruber, Benjamin D.; Delhaize, Emmanuel; White, Rosemary G.; James, Richard A.; You, Jiangfeng; Yang, Zhenming; Ryan, Peter R.
<x xml:space="preserve">Abstract</x> The barley (Hordeum vulgare) gene HvALMT1 encodes an anion channel in guard cells and in certain root tissues indicating that it may perform multiple roles. The protein localizes to the plasma membrane and facilitates malate efflux from cells when constitutively expressed in barley plants and Xenopus oocytes. This study investigated the function of HvALMT1 further by identifying its tissue‐specific expression and by generating and characterizing RNAi lines with reduced HvALMT1 expression. We show that transgenic plants with 18–30% of wild‐type HvALMT1 expression had impaired guard cell function. They maintained higher stomatal conductance in low light intensity and lost water more rapidly from excised leaves than the null segregant control plants. Tissue‐specific expression of HvALMT1 was investigated in developing grain and during germination using transgenic barley lines expressing the green fluorescent protein (GFP) with the HvALMT1 promoter. We found that HvALMT1 is expressed in the nucellar projection, the aleurone layer and the scutellum of developing barley grain. Malate release measured from isolated aleurone layers prepared from imbibed grain was significantly lower in the RNAi barley plants compared with control plants. These data provide molecular and physiological evidence that HvALMT1 functions in guard cells, in grain development and during germination. We propose that HvALMT1 releases malate and perhaps other anions from guard cells to promote stomatal closure. The likely roles of HvALMT1 during seed development and grain germination are also discussed.